THE IMPORTANCE OF PRINCIPLES OF JUSTICE AND HUMANITARIANISM IN ENSURING STATE SOCIAL POLICY AND DEVELOPMENT - Sherzod A. Xazratkulov (International Scientific and Current Research Conferences, 2022)
The article analyzes the principles of social protection, justice and humanity. The features of the emergence and development of state social protection are also highlighted. The stages of formation of the state's social protection and issues of improvement of the state's social goals were discussed.